Tetramicra brevifilum, a potential threat to farmed turbot Scophthalmus maximus - Figueras Huerta, Antonio; Novoa, Beatriz; Santarém, M. M.; Martínez, Emili; Álvarez, J. M.; Toranzo, A. E.; Dyková, Iva (Inter Research, 1992)
9 pages, 14 figures. The development of turbot Scophthalmus maximus culture has resulted in an increase of pathological problems involving mainly bacteria1 infections. During 1990, mortalities were detected in some grow-out facilities in Galicia, Spain, and were attributed to the microsporidian Tetramicra brevifilum Matthews & Matthews, 1980. The outbreak lasted for 3 1/2 mo. The start of the outbreak was associated with a drop in temperature. Affected fish showed an erratic swimming behaviour, swelling of different parts of the body, darkening of the dorsal surface, and overproduction of mucus on the surface of the body. Fish with a high intensity of infection had jelly-like muscles. Small xenomas formed by T brevifilum were found to be associated with regressive changes of the host tissue, with agglomerations of mature spores eliciting sometimes inflammatory reaction of the host. The agglutinin titers detected in naturally infected fish were low. There was a light host response. Electrophoresis of sera from naturally infected fish showed an additional protein band (molecular weight: 128 kDa) not found in uninfected samples. Results suggest that although turbot infected with microsporidians are immunologically impaired, the immunodepression does not increase the susceptibility of fish to vibriosis. This work was supported by the Grant MAR91-1133- C02-02 from the Comisión lnterministenal de Ciencia y Tecnología (CICYT) Spain. B. Novoa acknowledges the Ministerio de Educación y Ciencia (Spain), and María Santarém the Junta Nacional de Investigaçio Científica e Tecnológica (Portugal), for research fellowships. Peer reviewed